SAFETY AND PERFORMANCE CONSIDERATIONS FOR INTERACTIONS BETWEEN ELECTROMAGNETIC FIELDS AND BIOLOGICAL TISSUE: APPLICATIONS TO HIGH FIELD HUMAN MAGNETIC RESONANCE IMAGING AND TISSUE-IMPLANTED DEVICES - (:unkn) unknown (My University, 2010)
The principal advantage of magnetic resonance imaging (MRI) at high field is the increase in signal to noise ratio (SNR), however, high field imaging also leads to an increased Larmor (operating) frequency, thus the wavelength in tissue can become comparable to the size of the load and/or the coil. The performance of the radiofrequency (RF) coil, as a result, becomes increasingly dependent on its electromagnetic interactions with the load, human body or head.

Invasive brain machine interface (BMI) technology uses implanted microelectrodes to capture the action potentials of many individual neurons, especially those that code for movement or its intent. Traditionally, stimulating nerves or brain tissue involves cumbersome wiring to power/communicate with the chip. To avoid the limit of the BMI's mobility and freedom, RF powered wireless implementation of a BMI chip has been proposed to widely extend BMI applications. It is essential to perform an analysis of electromagnetic power deposition throughout the human head to determine the amount of power available to BMI devices.

In this dissertation, a complete electromagnetic computational (full wave) analysis, the finite difference time domain (FDTD) method, is applied to calculate the interaction between the radio frequency (RF) magnetic field and the subjects during ultra high field MRI exams and wireless BMI operations. The interactions between the high frequency RF fields with the human head and the body models severely affect the performances of MRI and BMI operations, and they also cause heating safety concerns to the tissues exposed to the RF radiation. Through precisely numerical calculations, we accomplished in this dissertation 1) an improved optimization scheme using variable phase and variable amplitude excitation to improve the performance of RF transverse electromagnetic (TEM) coils in MRI with safety concerns; and 2) evaluations of the performance and safety for a prototype of the wireless invasive BMI. Temperature changes caused by RF power deposition are calculated in both MRI and BMI applications.
Keywords: Magnetic resonance imaging; Brain-computer interfaces; Electromagnetic compatibility; Electromagnetic fields--Health aspects